Do candidate reactions relate to job performance or affect criterion-related validity? A multistudy investigation of relations among reactions, selection test scores, and job performance - MCCARTHY, Julie (Institutional Knowledge at Singapore Management University, 2013)
Considerable evidence suggests that how candidates react to selection procedures can affect their test performance and their attitudes toward the hiring organization (e.g., recommending the firm to others). However, very few studies of candidate reactions have examined one of the outcomes organizations care most about: job performance. We attempt to address this gap by developing and testing a conceptual framework that delineates whether and how candidate reactions might influence job performance. We accomplish this objective using data from 4 studies (total N = 6,480), 6 selection procedures (personality tests, job knowledge tests, cognitive ability tests, work samples, situational judgment tests, and a selection inventory), 5 key candidate reactions (anxiety, motivation, belief in tests, self-efficacy, and procedural justice), 2 contexts (industry and education), 3 continents (North America, South America, and Europe), 2 study designs (predictive and concurrent), and 4 occupational areas (medical, sales, customer service, and technological). Consistent with previous research, candidate reactions were related to test scores, and test scores were related to job performance. Further, there was some evidence that reactions affected performance indirectly through their influence on test scores. Finally, in no cases did candidate reactions affect the prediction of job performance by increasing or decreasing the criterion-related validity of test scores. Implications of these findings and avenues for future research are discussed.